Nurturing reflective learners in mathematics - Kaur, Berinderjeet, 1955- (Yearbook (Association of Mathematics Educators (Singapore)), 2013)
This annual volume focuses on a single theme in mathematics education. The objective is to encourage teachers and researchers to advance reflection among students and teachers in mathematics classrooms. Published jointly with the Association of Mathematics Educators in Singapore.